A systematic review of iron supplementation’s effects on adolescent girls - Silitonga, Hanna Tabita Hasianna; Salim, Lutfi Agus; Nurmala, Ira (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Anaemia is a nutritional problem that mostly affects adolescent girls around the world and has become a public health problem in many countries. Iron supplementation is one of public health intervention used to prevent adolescents from iron deficiency anaemia. Various countries have widely applied this program to reduce and prevent anaemia in adolescent and pregnant women.Objectives: Therefore, this literature review will discuss the effects of iron supplementation program on adolescent girls.Materials and Methods: This study was a systematic literature review of eight articles. These articles were found from scientific journal articles from five databases (Proquest, Science direct, EbscoHost, Pubmed, SAGE).Results: Our study showed iron supplementation in adolescent girls increased haemoglobin status, serum ferritin and decreased anaemia prevalence.Conclusion: Initiatives for iron supplementation programs among adolescent girls are necessary to reduce iron deficiency anaemia.